Estrutura genética espacial intrapopulacional em Stryphnodendron adstringens (barbatimão fabaceae) - Miranda, Alline Afonso do Nascimento Creado de (2020)
The Cerrado biome, despite containing one of the greatest biodiversity on the planet, undergoes constant deforestation due to the expansion of agricultural frontiers. The loss of natural territory consequently leads to the loss of genetic diversity. This is worrying when it comes to native species, such as Stryphnodendron adstringens, popularly known as barbatimão. Therefore, it is important to know the characteristics of the biology of S. adstringens, in order to define efficient management and conservation strategies. In this context, the objective of this study was to evaluate genetic diversity, genetic flow (estimating the size of the neighborhood group), the presence of clones and the spatial genetic structure existing in a natural population of S. adstringens. For this, genomic DNA was extracted from the leaf tissue of 124 individuals, all georeferenced. For the amplification of the microsatellite regions, nine pairs of primers developed for the species were used. Based on the genotype matrix, analyzes of genetic diversity, effective size of inbreeding, cross-fertilization rate, spatial genetic structure and identity analysis were performed to verify the occurrence of clones. For the nine loci, a total of 74 alleles were found and an average of 8.2 alleles per location. The observed average heterozygosity (HO) was equal to 0.556 and the average genetic diversity (HE) was equal to 0.624. The inbreeding coefficient (f) was significant and equal to 0.110, showing an excess of homozygotes. The genetic diversity in the population was considered high, with 71% of the maximum expected heterozygosity. The crossing system was considered mixed based on the cross fertilization rate (t ̂a) equal to 0.80. The effective size of the consanguinity (Nef) was 111.72; corresponding to a genetic representation of 0.90, indicating that there is no genetic deviation in the population. There was a significant spatial genetic structure in the first distance class with pairs of up to 49 meters. A Sp statistic equal to 0.0095 was considered moderate and associated with the genetic neighborhood (Nb = 105.3) demonstrated that pollen dispersion is efficient to maintain genetic diversity in the population. Ten groups of individuals with identical genotypes were found for nine sites used, suggesting the occurrence of vegetative reproduction. The results plan was possible, which, for the formation of germplasm banks, is collected at a minimum distance of 49 meters between the guaranteed items, in addition to contemplating the genetic diversity present in the population.